AN ANALYSIS OF GRAMMATICAL ERRORS IN WRITING RECOUNT TEXT AT THE FIRST YEAR CLASSES OF ENGLISH DEPARTMENT - Martiarini, Elyza; Candra, Eva Nurul (Jurnal Ilmiah Bina Bahasa, 2019)
The objective of this research is to find out and analyze the types of error made by students at the first-year classes in writing a recount text. The methodology of the research used is qualitative methods and the research design is a case study. Moreover, the writers chose the first-year classes students of English Department and observed 40 students. The writers used a written test to gain the data about error in writing a recount text. Based on the analysis of students? recount text writing, there were several mistakes made by the students, with the total number of percentages was 76%. Of these, 76% errors including 15% errors of irregular verb usage, 12% errors of regular verb, and the type of error most often done by the students was 32% errors of word choice, 2% errors of omission, 3% errors of auxiliary verb, 5% errors of intralingual transfer, 2% errors of adverb, error of misordering was 5%, and error of unclear meaning was only 2%. The number errors of be was 17%, and the use of personal pronoun errors was 7%.